Efficacy of Concentrated Growth Factor with Autograft and Xenograft in Mandible Fractures: A Randomized Clinical Trial: - - Malik, Samreen; Abdul Hafeez Shaikh; Tahera Ayub; Amna Rehman; Hijab Farid Khan; Arifa Haque (Journal of University College of Medicine and Dentistry, 2024)
Objective: To evaluate the efficacy of adjuvant therapy with Concentrated Growth Factor (CGF) along with xenograft and autograft in mandible fractures, in terms of bone density gain and healing over the period of 6 months. Methodology: This was a Randomized Clinical Trial conducted at a public sector tertiary care hospital in Karachi from May 2019 to July 2022. It included patients with mandible fractures requiring bone grafts due to non-union, delayed union, or mal-union. The patients were divided into three groups, each consisting of 20 patients. Group A underwent mandibular surgery using autograft alone, Group B received autograft combined with CGF, and Group C received xenograft combined with CGF. The participants were monitored using serial cone-beam computed tomography at the 4th and 6th months post-operatively to evaluate bone healing and bone density. By the end of the study, all cone-beam CT scans were evaluated for bone density. Results: The results showed a significant increase in bone bulk formation across all three groups between the 4th and 6th month, highlighting the effectiveness of all treatment modalities (p < 0.001). However, intergroup comparison revealed that bone density was comparatively higher in groups B and C, where CGF was used as an adjuvant, than in group A. However, the mean difference in bone density over the 6 months period was similar for Group A (-229.2) and Group B (-227.7), while Group C showed a slightly greater mean difference of -237.9 Conclusion: CGF is equally effective with both autograft and xenograft. However, using CGF with xenograft is preferable, as it helps avoid donor site morbidity and reduces patient inconvenience associated with autograft harvesting. Key words: Autograft, Concentrated Growth Factor, Xenograft, Cone Beam Computed Tomography, Mandible